Axial flux machine with non-slotted torus-ns rotor type. Design and investigate for electric traction - Larbi, B.; Hatti, M.; Kouzi, K.; Ghadbane, A. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2023)
Introduction. The drive electric motor is one of the key components in the traction chain of an electric vehicle. Traditional radial flux motors used in electric vehicles, which use permanent magnets or induction motors in an electric field, are experiencing significant development aimed at optimizing their weight and cost. However, it can only go so far, so switching to a completely different type of machine, such as an axial flow, might be a good alternative. The novelty to this item is an axial flux permanent magnet motorization with non-slotted TORUS-NS rotor (single interior stator with two external rotors North-South) type housed in the wheel of the vehicle; this allows power to pass directly from the motor to the wheel, increasing the efficiency of the motor. System complexity is also less, as the transmission, differentials and driveshaft are eliminated. Purpose is to equip the electric car and choose the motor adapted to the application and the available space. The smaller size and weight allows for a lighter vehicle and more batteries, thus increasing range. The focus on customization is because vehicle performance is so dependent on the quality of the vehicle architecture , battery pack and axial flux motor design. The results obtained are in good agreement of accuracy, in particular the flux density at the air gap. The investigation is carried out by the finite element method. Machine model was run on Maxwell 16.0 business code.